1999
DOI: 10.1021/om980979l
|View full text |Cite
|
Sign up to set email alerts
|

Multi-insertion Reactions of Isocyanides with Zirconium Amido Silyl Complexes

Abstract: The reactions of (Me 2 N) 3 ZrSi(SiMe 3 ) 3 (1), (Me 2 N) 3 ZrSiPh 2 Bu t (THF) 0.5 (2), and (Me 2 N) 2 [(Me 3 -Si) 2 N]ZrSi(SiMe 3 ) 3 (3) with 2,6-dimethylphenyl isocyanide (ArNC) or tert-butyl isocyanide (Bu t NC) have been investigated. The first ArNC was found to insert exclusively into the Zr-Si bond in complex 3 and, in contrast, into the Zr-N bonds in complex 1. Up to 4 equiv of ArNC react with 1 and 2 to give 7), and Zr[η 2 -C(NMe 2 )dNAr] 3 [η 2 -C(SiPh 2 Bu t ) dNAr] (8). However, 3 reacts with only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 83 publications
(49 reference statements)
3
16
0
1
Order By: Relevance
“…Similar features were reported for a2 -aza-1-zirconacyclo-3,4-dieneb y (14), C1ÀN1 1.152(2), C2ÀN2 1.324(2), C2ÀC3 1.374(2), C3ÀN3 1.468(2), C3ÀC4 1.428(2), C4ÀC5 1.209(3) ;N1-C1-Zr1 170. 17(15), N2-C2-C31 40.00 (16),N 2-C2-Zr1 69.84(9), C3-C4-C51 77.7(2); 5c:Zr1ÀC1 2.3363 (14), Zr1ÀC2 2.2346 (14), Zr1ÀN2 2.2046(12), C1ÀN1 1.1575 (18), C2ÀN2 1.3301 (17), C2ÀC3 1.3792(18), C3ÀSi1 1.8651(15), C3ÀC4 1.4343(19), C4ÀC5 1.205(2);N1-C1-Zr1 179.23(12), N2-C2-C31 34.07 (13), N2-C2-Zr1 71.33 (8),C 3-C4-C5 167.34(15). Chem.…”
Section: Resultsmentioning
confidence: 99%
“…Similar features were reported for a2 -aza-1-zirconacyclo-3,4-dieneb y (14), C1ÀN1 1.152(2), C2ÀN2 1.324(2), C2ÀC3 1.374(2), C3ÀN3 1.468(2), C3ÀC4 1.428(2), C4ÀC5 1.209(3) ;N1-C1-Zr1 170. 17(15), N2-C2-C31 40.00 (16),N 2-C2-Zr1 69.84(9), C3-C4-C51 77.7(2); 5c:Zr1ÀC1 2.3363 (14), Zr1ÀC2 2.2346 (14), Zr1ÀN2 2.2046(12), C1ÀN1 1.1575 (18), C2ÀN2 1.3301 (17), C2ÀC3 1.3792(18), C3ÀSi1 1.8651(15), C3ÀC4 1.4343(19), C4ÀC5 1.205(2);N1-C1-Zr1 179.23(12), N2-C2-C31 34.07 (13), N2-C2-Zr1 71.33 (8),C 3-C4-C5 167.34(15). Chem.…”
Section: Resultsmentioning
confidence: 99%
“…The preference of the Zr-N over Zr-C insertion observed in the above reactions is a very rare example [40] , because the insertion into M-N bonds would be possible only if no alkyl substituents are present [41,42] . These results prompt us to investigate the relative reactivity of M-C alkyl , M-C cage , and M-N bonds toward unsaturated substrates.…”
Section: Relative Reactivity Among M-c Cage M-n and M-c Alkyl Bondsmentioning
confidence: 99%
“…Many studies of competitive insertion of carbon monoxide and isocyanides into different M -C [1-3], M -Si [4,5] and M-N [1c, 6 -8] bonds have been reported. However there are many fewer reports of the competitive reactivity of M -C, M -O, M -N and M-Si bonds in insertion reactions of N CR, O CO, O CR 2 , S CS, O C NR and other related unsaturated substrates [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…However there are many fewer reports of the competitive reactivity of M -C, M -O, M -N and M-Si bonds in insertion reactions of N CR, O CO, O CR 2 , S CS, O C NR and other related unsaturated substrates [2,3]. Studies of CO 2 insertion reactions established that the M-amide bonds were more reactive than M-alkyl and M -alkoxo bonds, and that regioselective insertion into the M -amide bonds always takes place [3,9] except for the h 5 -cyclopentadienyl silyl-hamide zirconium dimethyl complex [Zr{h 5 -C 5 H 4 SiMe 2 -h-N t Bu}Me 2 ] for which previous regioselective insertion into the Zr -Me bonds was reported [10]. Mechanistic studies revealed [2] that direct nucleophilic attack on CO 2 by the amido ligand followed by O-coordination to the metal is more plausible than the initial coordination of CO 2 to the metal.…”
Section: Introductionmentioning
confidence: 99%